ICT outsourcing in public sector: relationship intensity among vendor and client / Aidura Bahak Udin - Bahak Udin, Aidura (Faculty of Computer and Mathematical Sciences, 2007)
Malaysia has its own recipe of building a long term success in ICT industry. Since the Multimedia Super Corridor (MSC) was conceptualized in 1996, Multimedia Development Corporation (MDeC) has been tasked to develop the unique corridor into a regional operation and as a home for global ICT companies. The overall of this research is all about the ICT outsourcing in public sector. The aims of this research are to identify the SLA problems the organizations, the factors that influence the relationship intensity among vendor and client and the effect of use of CRM in ICT outsourcing. In order to achieve the aims of this research, a research model was used to develop the research instrument for this study. The primary data for this research was collected by means of a questionnaire survey conducted among Malaysian public sector organizations. There are about 50 federal government agencies based in Putrajaya. Out of that, 28 federal government agencies and 12 state federal government agencies (within Klang Valley) were selected to participate in the survey. A total of 285 questionnaires were distributed among the selected organizations and within one and half months, questionnaires were returned. Although the research was conducted successfiilly, several limitations were encountered. The limitations are time constraint, limited academic reference on ICT outsourcing based in Malaysia and lack of cooperation during field study. The findings fi-om this research indicated the relationship among vendor and client and how significant the factors influence it. Problems that inherent in SLA also will be identified.